Gender differences in preferences of adolescents: Evidence from a large-scale classroom experiment - Dániel Horn; Hubert János Kiss; Tünde Lénárd (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
In this study, we estimate unadjusted and adjusted gender gap in time preference, risk attitudes, altruism, trust, trustworthiness, cooperation and competitiveness using data on 1088 high-school students from 53 classes. These data, collected by running incentivized experiments in Hungarian classrooms, are linked to an administrative data source on the students' standardized test scores, grades and family background. We find that after taking into account class fixed effects, females are significantly more altruistic (both with classmates and schoolmates), but are less present-biased, less risk tolerant, less trusting, less trustworthy and less competitive than males. At the same time we do not observe significant gender differences in patience, time inconsistency and cooperation at the 5% significance level. We also show that these initial gender differences do not change even if we control for age, family background, cognitive skills and school grades in a regression framework. Moreover, the gender gap also remains in all but one of these preferences even if we control for the other preference domains, suggesting that only risk preferences are confounded by the other preferences, at least as the gender gap in these preferences is concerned.
Keywords: C80; C90; D91; 330; adolescents; altruism; competitiveness; cooperation; dictator game; patience; present bias; public goods game; risk preferences; social preferences; time inconsistency; time preferences; trust; trustworthiness